Leader Organizational Citizenship Behaviour and Perceived Followers Support as Outcomes of Proactive Followership: A Social Exchange Perspective (Pakistan Business Review, 2024)
In recent decades, leadership research has tended to focus on leaders and the role of followers has been given less attention. This study, which uses the social exchange theory, investigates the role of proactive followership in leadership outcomes, considering the moderating influence of individual-level power distance orientation (PDO). Non-probability sampling was employed to tests the proposed hypotheses, 182 respondents participated in the research. The data was analysed using SmartPLS 3. The results showed that proactive followership has a positive effect on leader organizational citizenship behaviour (OCB) and the perceived support of followers. PDO significantly moderates the relationship between proactive followership and leader OCB, with low PDO strengthening the role of proactive followers in shaping leader OCB. These findings suggest that organizations should focus on developing their followers in order to improve leadership outcomes and strengthen relationships.